Contextual Problems of Interpretation of P. A. Oyunsky’s Personality as a Writer-Philosopher - Okorokova, Varvara Borisovna; Permyakova, Tuyara Nikolaevna (Journal of History Culture and Art Research, 2018)
This paper presents the problems of interpretation of Platon Alekseyevich Oyunsky’s (1893-1939) personality, the Yakut classic writer, in terms of his self-identification, finding his place in literature, society and, in general, history, his struggle for truth and universal human values. The article uses a set of such traditional methods as historical-functional, typological and comparative. Interpretation of P. Oyunsky’s contextual levels of creativity will allow to delve into the creative core of the writer, and reveal both his tasks and achievements in fiction. In the end of the analysis of the writer’s creativity contexts, the integrity of his personality will be revealed. The artistic concept of Oyunsky’s reality is realized in his philosophical works – “Nyukuus the Madman”, “The Red Shaman”, “Kudangsa the Great”, “Alexander the Great”, which become the starting point for the evolution of his worldview. The writer was looking for answers not only to hot-button issues of society, but he also talked about universal and eternal problems of existence. Particular attention was paid to the creation of heroic characters, fighting for the happiness of the people and changing the world. Oyunsky created Yakut literature of a new type, he became a writer of romanticism. The study of the literary context in the writer’s work presupposes insight into the semantic depths of works to comprehend the author’s concept of reality. Oyunsky, as a writer-philosopher, reflected on the universal problems of life and death, the appointment of man and his fate, the role of great people in history, the struggle between Good and Evil, Mind and Force. Oyunsky showed the triumph of Mind in his works, the eternal truths of mankind and foresaw that thanks to creativity, his name will not be forgotten by the people.